DETERMINAN KEUNGGULAN KOMPARATIF PRODUK KOPI INDONESIA DALAM PERDAGANGAN INTERNATIONAL TAHUN 1986- 2015 - Suyastiningsih, Ni putu Eva; Setyari, Ni Putu Wiwin; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
ABSTRACT The aim of research to determine the comparative advantage coffee exports in international period 1986-2015, and impact comparative advantage coffee exports in international perdangangan period 1986-2015. Thestudy was conducted in Indonesia by using literature. Data collection techniques with direct recording data about data rates, with dollar exchange and tariff analysis techniques Revcaled Index Comparative lenier adventage and multiple regression.Based analysis concludedIndonesian state has value of coffee export competitiveness is high with average values ??? 1. Value RCA meaningful comparative advantage of Indonesia's coffee exports 1986-2015 period have contributed and high competitiveness compared to other countries in international market. Coffee prices partially negativeeffect on comparative advantage of Indonesia's coffee exports in international period 1986-2015. The rupiah against  US Dollar and Tariff significant positive effect partially comparative advantage of Indonesia coffee exports in the international trading period 1986-2015 Keywords : Coffee Prices, The US Dollar Exchange, Tariff rate change And Comparative Advantage